Factors Influencing Emerging Market Central Banks' Decision to Intervene in Foreign Exchange Markets - Malloy, Matthew (IMF Working Papers; Working Paper ;, 2013)
Using panel data for 15 economies from 2001-12, I identify determinants of central bank foreign exchange intervention in emerging markets ('EMs') with flexible to moderately managed exchange rates. Similar to other studies, I find that central banks tend to 'lean against the wind,' buying/selling more foreign exchange in response to greater short-run and medium-run appreciation/depreciation pressures. The panel structure provides a framework to test whether other macroeconomic variables influence the different rates of reserve accumulation between economies. In testing other variables, I find evidence of both precautionary and external competitiveness motives for reserve accumulation.